Observational Study of Pediatric Cochlear Implant Recipients: Two-year Follow-up Outcomes - Sidika CESUR; Ayca CIPRUT; Sengul TERLEMEZ (Medeniyet Medical Journal)
Objective: The aim of this study was to evaluate the improvements in quality of life and auditory performance via a descriptive report using patient-related outcomes measures in a group of children with cochlear implants (CI). Methods: This was a longitudinal and retrospective study based on the analysis of patient records of a total of 28 children with CI, 18 of whom had bilateral (64.3%) and 10 had unilateral (35.7%). The study included repeated within-subject measures of Hearing Implants Quality of Life (CuHI-QoL), Categories of Auditory Performance (CAP-II), Speech, Spatial, and Qualities of Hearing scale-Parents' version (SSQ-P) scales, and Implant Recipient Follow-up (IRF) form at 6-month intervals from baseline up to 24 months. Results: During the 2-year follow-up assessments, all children with CI showed statistically significant improvement over time in their CAPII, SSQ-P, CuHI-QoL, and IRF scores (p<0.001). The most significant increase in scores occurred within the first six months following the baseline and then continued to increase gradually at a slower pace over time. A moderate negative relationship was found between the age of implantation and SSQ-P and family satisfaction scores of IRF (p<0.05). Conclusions: Family expectations, overall well-being, quality of life, auditory, and verbal skills increase positively with earlier CI intervention. Moreover, the subjective assessment results showed that parents-positive attitudes toward implantation, and willingness to recommend it to others have steadily increased in time. Although the cohort is relatively small and variable, the results offer a descriptive view to outcomes in real-world practice.